4(4x+2)+7(x-1)=

Simple and best practice solution for 4(4x+2)+7(x-1)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(4x+2)+7(x-1)= equation:


Simplifying
4(4x + 2) + 7(x + -1) = 0

Reorder the terms:
4(2 + 4x) + 7(x + -1) = 0
(2 * 4 + 4x * 4) + 7(x + -1) = 0
(8 + 16x) + 7(x + -1) = 0

Reorder the terms:
8 + 16x + 7(-1 + x) = 0
8 + 16x + (-1 * 7 + x * 7) = 0
8 + 16x + (-7 + 7x) = 0

Reorder the terms:
8 + -7 + 16x + 7x = 0

Combine like terms: 8 + -7 = 1
1 + 16x + 7x = 0

Combine like terms: 16x + 7x = 23x
1 + 23x = 0

Solving
1 + 23x = 0

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1' to each side of the equation.
1 + -1 + 23x = 0 + -1

Combine like terms: 1 + -1 = 0
0 + 23x = 0 + -1
23x = 0 + -1

Combine like terms: 0 + -1 = -1
23x = -1

Divide each side by '23'.
x = -0.04347826087

Simplifying
x = -0.04347826087

See similar equations:

| f(x)=1-Ix-2I | | 5-3+2x=125 | | 9n-40= | | 7+4x-5+x+2x= | | en-2=12 | | 0=7+2x^2+4x-5 | | 2g^2-32=0 | | 10u+7=8[2u-4] | | 0.25m+2=4.50 | | x^2=-9x+15 | | -7[6x+7]=-42x-49 | | 10(1*3b)=-20 | | 6(3x+1)=5(4x+3) | | x^2+15x+35=-15 | | -7x-2(-x-8)=76 | | 2[5x-20]=10[x-20] | | (4j-3)-(2j+5)= | | 2.3x=8.28 | | 5(2+y)=3(y+6) | | -2[18-3y]=7y+2y | | 25n+0.12m=29.46 | | -2x^2+3x+-1=0 | | X^2+16y+32=0 | | z-(0.3)=-2.4 | | 15+15x=-125 | | 3y-12=-3x | | x^2-2x+3=5 | | 5-11t=7[5-2t] | | -8x+7=8x+2 | | 7v+11v^2-18v^2-16-3v+8= | | 30-0.003k=20 | | X+y=398 |

Equations solver categories